Clinical presentation and outcome of patients with enteric-type adenocarcinoma of the lung: A pooled analysis of published cases. (May 2023) - Fassi, Elena; Mandruzzato, Marcella; Zamparini, Manuel; Bianchi, Susanna; Petrelli, Fausto; Baggi, Alice; Alberti, Andrea; Grisanti, Salvatore; Berruti, Alfredo
Highlights: Advanced lung-ETAC seem to have a better prognosis compared to common NSCLC. Lung-ETAC shows a relevant mutational rate with several druggable genomic alterations. DNA mismatch repair deficiency (dMMR) is a relatively frequent event in lung-ETAC. Abstract: Enteric-type adenocarcinoma of the lung (lung-ETAC, former pulmonary enteric adenocarcinoma, PEAC) is a rare subtype of non-small cell lung cancer (NSCLC), which shares morphological and immunohistochemical features with lung and colorectal adenocarcinoma. Few data are available on patient prognosis, possible prognostic factors and systemic approach to metastatic disease. We performed a pooled analysis and a systematic review of published lung-ETAC, along with an additional case description. Thirty-one eligible publications were identified, providing data from 126 patients. In the 127 patients overall analyzed, median overall survival (OS) was 56.0 (range 36.7–75.3) months in early-stage patients and 14.0 (range 4.5–23.5) months in those with advanced/metastatic disease. Median disease-free survival (DFS) after radical surgery was 24 (range 22.6–35.1) months. Smoking status (HR 4.304, 95% CI: 1.261–14.693, p = 0.020) and node involvement (HR 1.853, 95% CI: 1.179–2.911, p = 0.007) were the negative independent prognostic factors at multivariate analysis. As regards systemic therapies for advanced cases, no firm conclusions were drawn about the efficacy of lung cancer-oriented chemotherapy regimens as opposed to colon cancer-oriented ones. Molecular analysis of lung-ETAC revealed a relatively high mutational rate, with alterations in several druggable molecular pathways, KRAS and NRAS (31%) were the most frequently mutated oncogenes, followed by ROS1 (15%), RET (13%), BRAF (11%), EGFR (8%) and ALK (6%). Moreover, 3 (15%) out of 20 cases showed DNA mismatch repair deficiency (dMMR). In conclusion, advanced lung-ETAC patients appeared to have a better prognosis compared to other subtypes of NSCLC. Moreover, the mutational rate and microsatellite instability found in lung-ETACs suggest that a significant proportion of these patients could benefit from target therapies and immunotherapy.